Clinical availability of nonalcoholic fatty liver disease as an early predictor of type 2 diabetes mellitus in korean men: 5‐year prospective cohort study1. Issue 4 (8th April 2013) - Park, Sung Keun; Seo, Mi Hae; Shin, Ho Cheol; Ryoo, Jae‐Hong
Abstract There have been several reports about the clinical association between type 2 diabetes mellitus (DM) and nonalcoholic fatty liver disease (NAFLD). However, most of the studies were about the unilateral effects of type 2 DM on NAFLD, and studies on the reverse relation are rare. Thus, this study was designed to investigate the effect of NAFLD on type 2 DM. We conducted a prospective cohort study on 25, 232 Korean men without type 2 DM for 5 years. We serially checked the various metabolic factors including fasting glucose and hemoglobin A1c (HbA1c), and monitored the development of type 2 DM. The incidence rate of type 2 DM was compared according to the degree of NAFLD (normal, mild, and moderate to severe), and a Cox proportional hazards model was used to measure the hazard ratios (HRs) of NAFLD on type 2 DM. The incidence rate of type 2 DM increased according to the degree of NAFLD (normal: 7.0%, mild: 9.8%, moderate to severe: 17.8%, P < 0.001). Even after adjusting for other multiple covariates, the HRs (95% confidence interval [CI]) for type 2 DM development was higher in the mild group (1.09; 0.81‐1.48) and moderate to severe group (1.73; 1.00‐3.01) compared to the normal group, respectively (P for trend <0.001). Conclusion: The development of type 2 DM is potentially more associated with more progressive NAFLD than a normal or milder state. In addition, NAFLD was an independent risk factor for the future development of type 2 DM. These results suggest the potential availability of NAFLD as an early predictor of type 2 DM. (HEPATOLOGY 2013;57:1378–1383)